2022
DOI: 10.3390/cancers14030594
|View full text |Cite
|
Sign up to set email alerts
|

New Insights on the Genetics of Pheochromocytoma and Paraganglioma and Its Clinical Implications

Abstract: Pheochromocytomas (PHEOs) and paragangliomas (PGLs) are rare neuroendocrine tumors that arise from chromaffin cells. PHEOs arise from the adrenal medulla, whereas PGLs arise from the neural crest localized outside the adrenal gland. Approximately 40% of all cases of PPGLs (pheochromocytomas/paragangliomas) are associated with germline mutations and 30–40% display somatic driver mutations. The mutations associated with PPGLs can be classified into three groups. The pseudohypoxic group or cluster I includes the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 96 publications
2
48
0
1
Order By: Relevance
“…Collectively, hereditary paraganglioma-pheochromocytoma (PGL/PCC) syndromes are rare neuroendocrine tumors with an estimated incidence of approximately 2-8 cases per million per year ( 9 ). Approximately 40% of all cases of PGL/PCC are associated with germline pathogenic variants ( 2 , 10 , 11 ) in the pseudo-hypoxic signaling pathway (cluster I), kinase signaling (cluster II), or Wingless and Int-1 (Wnt) signaling group (cluster III) ( Figure 3 ) ( 12 ). Pathogenic variants in the SDHx genes ( SDHA, SDHB, SDHC , and SDHD ) are classified under the cluster I genes which results in dysfunction of succinate dehydrogenase (SDH) leading to competitive inhibition of the enzyme, prolyl hydroxylase, involved in the degradation of hypoxia-inducible factor 1- α (HIF1- α) ( 2 , 13 , 14 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collectively, hereditary paraganglioma-pheochromocytoma (PGL/PCC) syndromes are rare neuroendocrine tumors with an estimated incidence of approximately 2-8 cases per million per year ( 9 ). Approximately 40% of all cases of PGL/PCC are associated with germline pathogenic variants ( 2 , 10 , 11 ) in the pseudo-hypoxic signaling pathway (cluster I), kinase signaling (cluster II), or Wingless and Int-1 (Wnt) signaling group (cluster III) ( Figure 3 ) ( 12 ). Pathogenic variants in the SDHx genes ( SDHA, SDHB, SDHC , and SDHD ) are classified under the cluster I genes which results in dysfunction of succinate dehydrogenase (SDH) leading to competitive inhibition of the enzyme, prolyl hydroxylase, involved in the degradation of hypoxia-inducible factor 1- α (HIF1- α) ( 2 , 13 , 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical features include cerebellar and spinal hemangioblastomas, renal cell cancer, neuroendocrine pancreatic tumor, pheochromocytoma, and paragangliomas. Germline pathogenic variants in the succinate dehydrogenase A ( SDHA ) gene are associated with familial paraganglioma and pheochromocytoma syndrome inherited in an autosomal dominant manner ( 2 ). At the cellular level, SDHA and VHL proteins interact and converge into a common molecular pathway via the hypoxia inducible factor alpha (HIF-α) ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have indicated that the frequency of germline variants of PPGLs is very high among all human tumors. Besides MAX , multiple new PPGL-related genes such as CSDE1 , H3F3A , MET , MERTK , UBTF-MAML3 , SLC25A11 , IRP1 , DLST , and SUCLG2 have been discovered in recent years [ 35 ]. With the expansion of our knowledge of genetics, new biomarkers and artificial intelligence can also help assess the metastatic risk and overall prognosis of each individual.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 5%-10% of all cancers are estimated to be attributable to hereditary cancer syndromes caused by germline variants in cancer predisposition genes, 1,2 however the proportion caused by germline variants varies widely across cancer types (eg, $2%-5% of colorectal cancers, 3 $24% of ovarian cancers, 4 $40% of paragangliomas/ pheochromocytomas 5 ).…”
Section: Hereditary Cancer Disease Etiologymentioning
confidence: 99%